Dual-media corrosion resistant composite ceramic material, heat exchanger and preparation method thereof

CN122916631APending Publication Date: 2026-10-16YICHANG KELISHENG IND CO LTD RESEARCH INSTITUTE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611330435.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0010]针对现有技术中所存在的不足,本发明提供了耐双介质腐蚀的复相陶瓷材料、换热器及制备方法,其解决了现有技术中存在的材料性能不足、生产工艺精度不够以及整体结构不匹配的问题

Benefits of technology

[0034] 1. This invention addresses the two completely different corrosion mechanisms of molten salt and SO2 by designing corresponding first and second surface layer structures. Under high-purity molten salt conditions, the first surface layer exhibits more than 20 times the resistance to chloride ion corrosion compared to pure SiC, while the second surface layer demonstrates significantly superior resistance to grain boundary oxidation corrosion compared to pure SiC. This enables the multiphase ceramic material of this invention to operate stably for extended periods under extreme dual-medium conditions at 800-900℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916631A_ABST
    Figure CN122916631A_ABST
Patent Text Reader

Abstract

The application provides a dual-media corrosion-resistant composite ceramic material, which comprises a first surface layer, a heat-conducting layer and a second surface layer arranged in sequence; further provided is a heat exchanger, which comprises a plurality of stacked ceramic heat exchange plates, a shell and a flexible sealing assembly; the application further provides a preparation method of the heat exchanger, which comprises the steps of raw material pretreatment, green body forming, degreasing and pre-sintering, semi-finishing, densification sintering, precision finishing and cleaning, sealing stacking, assembling and detection; the application sets the first surface layer and the second surface layer corresponding to two completely different corrosion mechanisms of molten salt and sCO2 respectively, so that the composite ceramic material can be operated stably for a long time under the extreme conditions of the two media at 800-900 DEG C; the green body is pre-sintered after the micro-channel is prepared, and then is densification sintered, so that the internal stress of the ceramic can be released better, the risk of sintering deformation of the green body is avoided, and the micro-channel processing yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of multiphase ceramic materials technology, and more particularly to multiphase ceramic materials resistant to dual-medium corrosion, heat exchangers, and preparation methods. Background Technology

[0002] Multiphase ceramic materials have been widely used in many cutting-edge industrial and engineering fields due to their excellent corrosion resistance, high temperature resistance, and wear resistance.

[0003] The solar thermal molten salt thermal storage-supercritical carbon dioxide (sCO2) power generation system is considered the fourth-generation core technology in the field of solar thermal power generation. It combines efficient thermal storage technology with advanced thermodynamic cycles to achieve high-efficiency, low-cost, and highly flexible clean energy power generation. Its workflow can be divided into three core steps: heat collection, where sunlight is reflected and concentrated onto the collector via a heliostat field to generate high-temperature heat energy; heat storage, where this heat energy is transferred to molten salt through a heat exchanger, heating and storing the molten salt; and power generation, where, when power generation is needed, the stored heat energy is used again through the heat exchanger to heat supercritical carbon dioxide (sCO2), driving a turbine to generate electricity.

[0004] The core component, the "heart" of this power generation system, is the supercritical carbon dioxide (sCO2) power generation module, also known as the sCO2 Brayton cycle. In this cycle, high-pressure sCO2 is heated (from the heat of the molten salt) and, like steam, drives a turbine to generate electricity. The sCO2, after performing work, is cooled, compressed, and then reheated, achieving recycling. The heat exchanger is the most critical component, handling the transfer of heat from the molten salt to the sCO2. It is the core bottleneck equipment determining the system's cycle efficiency and equipment lifespan. Considering the poor high-temperature resistance, susceptibility to thermal fatigue, and low heat transfer efficiency of existing plate and shell-and-tube heat exchangers, microchannel heat exchangers are gradually replacing traditional structures.

[0005] However, the conventional SiC-Si3N4 multiphase ceramic heat exchanger structure still has certain problems when used for supercritical carbon dioxide (sCO2) power generation:

[0006] 1. Traditional homogenized ceramic materials are unable to simultaneously withstand two completely different corrosion mechanisms: chloride ion corrosion from chloride molten salts and SO2 grain boundary oxidation corrosion. This makes them unsuitable for extreme dual-medium operating conditions. Especially in chloride molten salt environments, chloride ions rapidly penetrate grain boundaries, leading to corrosion cracking and resulting in short equipment lifespan and poor reliability.

[0007] 2. Traditional processes involve prefabricating microchannels from green blanks and then sintering them. This results in significant deformation after sintering, making it impossible to achieve high-precision sealing. Furthermore, the subsequent connection of heat exchanger plates requires ceramic diffusion welding, but the welding temperature for traditional homogeneous ceramic diffusion welding is ≥2000℃, close to the ceramic sintering temperature. This can easily lead to ceramic grain growth and performance degradation, placing extremely high demands on equipment, resulting in high energy consumption and high costs.

[0008] 3. The current heat exchanger's overall structure is a nickel-based alloy printed circuit board heat exchanger (PCHE) structure. Because it uses a combination of a metal alloy substrate and a ceramic heat exchanger body, it will cause problems such as ceramic-metal thermal expansion mismatch and cracking at high temperatures. In high-temperature molten salt environments, it will also experience grain boundary corrosion and creep failure, which seriously affects its service life.

[0009] Therefore, a better heat exchanger structure is needed to adapt to the rapidly developing solar thermal molten salt thermal storage-supercritical carbon dioxide (sCO2) power generation system. Summary of the Invention

[0010] To address the shortcomings of existing technologies, this invention provides a dual-medium corrosion resistant multiphase ceramic material, a heat exchanger, and a preparation method, which solves the problems of insufficient material properties, inadequate manufacturing process precision, and mismatched overall structure in existing technologies.

[0011] In a first aspect, the present invention proposes a dual-media corrosion resistant multiphase ceramic material, comprising a first surface layer, a thermally conductive layer and a second surface layer arranged sequentially, wherein the first surface layer and the second surface layer sandwich the thermally conductive layer inside to form an integral structure, and the thickness of the thermally conductive layer accounts for more than 80% of the total thickness.

[0012] The raw materials for the first surface layer include the following components: 75-85wt% α-Al2O3 powder, 10-20wt% β-SiC powder, 2-4wt% Y2O3 sintering aid, and 1-3wt% La2O3 sintering aid;

[0013] The raw materials of the thermally conductive layer include the following components: 50-60wt% β-SiC powder, 35-45wt% α-Si3N4 whiskers, 2-4wt% Yb2O3 sintering aid, and 1-3wt% Sc2O3 sintering aid;

[0014] The raw materials for the second surface layer include the following components: 85-95wt% α-Si3N4 powder, 3-8wt% β-SiC powder, 1-3wt% Y2O3 sintering aid, 0.5-1.5wt% Sc2O3 sintering aid, 1-3wt% h-BN nanosheets, and 1-3wt% 3Y-TZP nano ZrO2 powder.

[0015] Preferably, the β-SiC powder is a submicron-sized high-purity powder with a purity ≥99.9% and a particle size of 0.5-1μm; the α-Si3N4 whiskers have an aspect ratio ≥20 and a purity ≥99.5%; the Y2O3 sintering aid, La2O3 sintering aid, Yb2O3 sintering aid, and Sc2O3 sintering aid are all nano-sized powders with a purity ≥99.99%.

[0016] Preferably, in the second surface layer, the h-BN nanosheets are pre-coated with a 50-100 nm thick SiC layer by chemical vapor deposition, and the coated h-BN nanosheets have a particle size of 100-200 nm and a thickness of 10-20 nm.

[0017] Secondly, the present invention proposes a heat exchanger using the above-mentioned dual-media corrosion resistant multiphase ceramic material, comprising multilayer stacked ceramic heat exchange plates, a shell and a flexible sealing assembly. The ceramic heat exchange plates are made of the dual-media corrosion resistant multiphase ceramic material, and their two opposite sides are respectively a first surface layer and a second surface layer. The shell is sleeved on the outside of the stacked ceramic heat exchange plates, and the flexible sealing assembly is disposed between the shell and the stacked ceramic heat exchange plates.

[0018] The first surface layer is provided with a first microchannel, and the second surface layer is provided with a second microchannel. The first microchannel and the second microchannel are arranged alternately along the direction perpendicular to the flow, so that the planar areas on adjacent ceramic heat exchange plates that are not provided with the first microchannel or the second microchannel are mutually sealing surfaces.

[0019] Furthermore, the flexible sealing assembly includes an elastic ceramic fiber buffer bushing and a graphite composite sealing gasket, wherein the ceramic fiber buffer bushing is filled between the edge of the ceramic heat exchange plate stack and the outer shell, and the graphite composite sealing gasket is disposed at the upper and lower ends of the ceramic heat exchange plate.

[0020] Furthermore, the first microchannel is provided with herringbone ribs, the height of which is less than the depth of the first microchannel, and the included angle of the herringbone ribs is 30°-60°, and they are arranged at equal intervals along the fluid flow direction; the second microchannel is provided with rhomboid turbulence columns, which are arranged alternately along the fluid flow direction.

[0021] Preferably, the elastic ceramic fiber buffer bushing is a high-silica ceramic fiber woven structure with a thickness of 0.5-1mm and a compression of ≥15%; the graphite composite sealing gasket is a flexible graphite-stainless steel reinforced composite material with a thickness of 1-2mm.

[0022] Furthermore, a nanoporous calcium silicate ceramic heat insulation layer with a thickness of 10-20 mm is provided between the outer shell and the flexible sealing component; an alumina ceramic anti-corrosion coating with a thickness of 500-800 μm is sprayed on the inner wall of the outer shell.

[0023] Thirdly, the present invention also provides a method for preparing the above-mentioned heat exchanger, comprising the following steps:

[0024] S1. Raw material pretreatment: Weigh the raw material powder according to the formula of the first surface layer, the thermally conductive layer and the second surface layer in the multiphase ceramic material, add anhydrous ethanol solvent, ammonium polyacrylate dispersant and PVB binder in sequence, and ball mill for 24-48h to obtain three ceramic slurries with solid content ≥55wt% and viscosity 5000-10000mPa·s respectively.

[0025] S2. Green Body Forming: A multi-layer co-casting process is used to sequentially cast the first surface layer, the heat-conducting layer, and the second surface layer to form a three-layer integrated gradient structure green body in one step. The total thickness of the green body is controlled between 1.2-3.6 mm. Through a precision mold hot pressing process, corresponding first and second microchannels are pre-fabricated on the first and second surface layers respectively in the undried state of the green body. After drying at a constant temperature and humidity of 30-40℃ for 24-48 hours, ceramic green body plates with microchannel structures are obtained.

[0026] S3. Degreasing and Pre-sintering: Place the ceramic green sheet in a high-purity nitrogen atmosphere furnace and heat it to 600-800℃ at a rate of 0.5-1℃ / min. Degrease and hold for 2-4 hours to completely remove organic additives. Then heat it to 1200-1400℃ at a rate of 2-3℃ / min and pre-sinter for 2-3 hours to obtain a pre-sintered green body with a density of 75%-85%.

[0027] S4. Semi-finishing: The sealing surface and positioning holes of the pre-sintered blank are semi-finished using a diamond grinding wheel, with dimensional accuracy controlled within ±20μm and surface roughness Ra≤1.6μm; then ultrasonically cleaned with anhydrous ethanol for 10-20min and vacuum dried at 100℃ for later use.

[0028] S5. Densification sintering: The semi-finished green body is placed in a high-purity nitrogen atmosphere sintering furnace and heated to 1850-1950℃ at a rate of 4-6℃ / min and held for 2-4 hours for pressureless densification sintering. After completion, it is cooled to room temperature with the furnace to obtain ceramic heat exchange plates with microchannel structure and a density ≥99.5%.

[0029] S6. Precision trimming and cleaning: The first microchannel, the second microchannel, and the sealing surface of the sintered ceramic heat exchange plate are precisely trimmed using a femtosecond laser to remove slight deformations during the sintering process. The dimensional accuracy is controlled within ±2μm, and the surface roughness Ra of the sealing surface is ≤0.2μm. After ultrasonic cleaning with anhydrous ethanol for 20-30 min, the plate is vacuum dried at 120℃ for 12 h for later use.

[0030] S7. Sealing and Stacking: Pre-coat the sealing surface of the ceramic heat exchange plate with a 10-20μm thick layer of nano-sized ceramic powder solder. The solder composition is consistent with the composition of the heat-conducting layer, and the particle size is 20-50nm. Align and stack the multi-layer ceramic heat exchange plates, place them in a high-purity nitrogen atmosphere diffusion welding furnace, and keep them at 1650-1750℃ and 1-5MPa for 1-3 hours to achieve low-temperature diffusion welding sealing.

[0031] S8. Assembly and Inspection: The welded ceramic heat exchange plates are stacked into the shell. The flexible sealing component uses an elastic ceramic fiber buffer bushing and a graphite composite gasket to achieve a flange-type flexible seal. After assembly, the air tightness test, pressure test, and heat exchange performance test are carried out in sequence. The finished product is obtained after passing the test.

[0032] Preferably, in step S2, the pressure of the precision mold hot pressing process is 5-10 MPa, the holding time is 30-60 s, and the hot pressing temperature is 25-35℃.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. This invention addresses the two completely different corrosion mechanisms of molten salt and SO2 by designing corresponding first and second surface layer structures. Under high-purity molten salt conditions, the first surface layer exhibits more than 20 times the resistance to chloride ion corrosion compared to pure SiC, while the second surface layer demonstrates significantly superior resistance to grain boundary oxidation corrosion compared to pure SiC. This enables the multiphase ceramic material of this invention to operate stably for extended periods under extreme dual-medium conditions at 800-900℃.

[0035] 2. The thermal conductive layer of the present invention adopts a SiC-Si3N4 whisker multiphase structure, which takes into account both high thermal conductivity and high fracture toughness, and improves the fracture toughness by more than 70% compared with pure SiC ceramics; at the same time, the room temperature thermal conductivity of the thermal conductive layer is ≥130W / (m·K), which far exceeds that of existing traditional ceramic materials, and can effectively realize heat transfer.

[0036] 3. In this invention, the green body undergoes a pre-sintering process after the prefabrication of microchannels, followed by densification sintering. This process can better release the internal stress of the ceramic, avoid the risk of deformation during green body sintering, and improve the yield of microchannel processing. At the same time, it achieves low-difficulty semi-finishing, improves the accuracy of the sealing surface, and, together with the sintering aids of the first and second surface layers and the additional nano solder, achieves low-temperature diffusion welding below 1750°C. This reduces the welding temperature by more than 250°C compared to traditional processes, reduces energy consumption by 40%, and avoids the problems of ceramic grain growth and performance degradation caused by high-temperature welding.

[0037] 4. The ceramic heat exchange plates of this invention are sealed with a flexible sealing assembly consisting of an elastic ceramic fiber buffer bushing and a graphite composite sealing gasket between them and the metal outer shell. This assembly can fully release the thermal stress caused by the difference in thermal expansion, reducing the risk of ceramic cracking during heating and cooling. Furthermore, the three-layer gradient composite ceramic structure has a matched coefficient of thermal expansion, eliminating the risk of interfacial delamination cracking. This ensures that its design stress is ≤1 / 3 of the material's high-temperature creep limit, and the creep deformation under 750℃ conditions for 100,000 hours is ≤0.1%, fully meeting the requirements for long-term operation. Attached Figure Description

[0038] Figure 1 This is a process flow diagram of an embodiment of the present invention.

[0039] Figure 2 This is a schematic diagram of the heat exchanger structure according to an embodiment of the present invention.

[0040] Figure 3 This is a schematic diagram of the staggered arrangement of microchannels on the ceramic heat exchange plate according to an embodiment of the present invention.

[0041] In the above figures: 1. Outer shell; 2. Ceramic fiber buffer bushing; 3. Graphite composite sealing gasket; 4. Ceramic heat exchange plate; 41. First microchannel; 42. Second microchannel. Detailed Implementation

[0042] The technical solutions of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0043] Example 1:

[0044] This embodiment provides a high-temperature heat exchanger adapted to a 1MW-level distributed solar thermal molten salt-sCO2 power generation system. Specific parameters are as follows:

[0045] Multiphase ceramic materials resistant to dual-media corrosion:

[0046] It includes a first surface layer, a thermally conductive layer, and a second surface layer, which are sequentially arranged. The first surface layer corresponds to the molten salt side, and the second surface layer corresponds to the sCO2 side. The total thickness is 2mm, with the first surface layer being 100μm, the thermally conductive layer being 1800μm, and the second surface layer being 100μm.

[0047] The raw materials for the first surface layer include the following components: 80wt% α-Al2O3 powder, 15wt% β-SiC powder, 3wt% Y2O3 sintering aid, and 2wt% La2O3 sintering aid;

[0048] The raw materials for the thermally conductive layer include the following components: 55wt% β-SiC powder, 40wt% α-Si3N4 whiskers, 3wt% Yb2O3 sintering aid, and 2wt% Sc2O3 sintering aid;

[0049] The raw materials for the second surface layer include the following components: 90wt% α-Si3N4 powder, 3wt% β-SiC powder, 2wt% Y2O3 sintering aid, 1wt% Sc2O3 sintering aid, 2wt% h-BN nanosheets, and 2wt% 3Y-TZP nano-ZrO2 powder. The h-BN nanosheets are pre-coated with a 75nm thick SiC layer by chemical vapor deposition. The coated h-BN nanosheets have a particle size of 150nm and a thickness of 15nm.

[0050] Among them, β-SiC powder is a submicron-sized high-purity powder with a purity ≥99.9% and a particle size of 0.5-1μm; α-Si3N4 whiskers have an aspect ratio ≥20 and a purity ≥99.5%; Y2O3 sintering aid, La2O3 sintering aid, Yb2O3 sintering aid, and Sc2O3 sintering aid are all nano-sized powders with a purity ≥99.99%.

[0051] like Figure 2 As shown, this embodiment also provides a heat exchanger using the aforementioned dual-medium corrosion-resistant multiphase ceramic material, with the following specific structure:

[0052] The system comprises 50 stacked ceramic heat exchange plates 4, a shell 1, and a flexible sealing assembly. The ceramic heat exchange plates 4 are made of the aforementioned dual-media corrosion-resistant multiphase ceramic material, with their two opposite sides being the first surface layer and the second surface layer, respectively. The shell 1 is fitted onto the stacked ceramic heat exchange plates 4. The ceramic heat exchange plates 4 have dimensions of 300mm × 300mm × 2mm.

[0053] The flexible sealing assembly includes an elastic ceramic fiber buffer bushing 2 and a graphite composite sealing gasket 3. The ceramic fiber buffer bushing 2 is filled between the edge of the ceramic heat exchange plate stack 4 and the outer shell 1, and the graphite composite sealing gasket 3 is located at the upper and lower ends of the ceramic heat exchange plate 4. The elastic ceramic fiber buffer bushing 2 is a high-silica ceramic fiber woven structure with a thickness of 0.8 mm and a compression of ≥15%. The graphite composite sealing gasket 3 is a flexible graphite-stainless steel reinforced composite material with a thickness of 1.5 mm and is mechanically compressed using a flange.

[0054] like Figure 3As shown, a first microchannel 41 is provided on the first surface layer, with dimensions of 500μm wide, 300μm deep, and a spacing of 800μm. Inside the first microchannel 41, there are 50μm high herringbone ribs, the height of which is less than the depth of the first microchannel 41, and the included angle of the herringbone ribs is 45°. These ribs are evenly spaced along the fluid flow direction. A second microchannel 42 is provided on the second surface layer, with dimensions of 200μm wide, 200μm deep, and a pitch of 400μm. Inside the second microchannel 42, there are diamond-shaped baffles, which are staggered along the fluid flow direction. The first microchannel 41 and the second microchannel 42 are staggered perpendicular to the flow direction, so that the planar areas on adjacent ceramic heat exchange plates 4 without the first microchannel 41 or the second microchannel 42 act as sealing surfaces for each other.

[0055] A 15mm thick nanoporous calcium silicate ceramic heat insulation layer is also provided between the outer shell 1 and the flexible sealing component; an alumina ceramic anti-corrosion coating with a thickness of 600μm is sprayed on the inner wall of the outer shell.

[0056] like Figure 1 As shown, the method for preparing the above-mentioned heat exchanger includes the following steps:

[0057] (1) Raw material pretreatment: Weigh the raw material powder according to the formula of the first surface layer, the heat-conducting layer and the second surface layer in the multiphase ceramic material, add anhydrous ethanol solvent, ammonium polyacrylate dispersant and PVB binder in sequence, and ball mill for 36 hours to obtain three ceramic slurries with solid content ≥55wt% and viscosity 8000mPa·s respectively.

[0058] (2) Green body forming: A multi-layer co-casting process is adopted, in which the first surface layer, the heat-conducting layer and the second surface layer are cast in sequence to form a green body with a three-layer integrated gradient structure in one go. The total thickness of the green body is controlled at 2.4 mm. Through a precision mold hot pressing process, the pressure is controlled at 8 MPa, the holding time is 45 s and the hot pressing temperature is 30 ℃. In the state of the green body not drying, the corresponding first microchannel and second microchannel are pre-made on the first surface layer and the second surface layer respectively. After drying at 35 ℃ constant temperature and humidity for 36 h, a ceramic green body plate with microchannel structure is obtained.

[0059] (3) Degreasing and pre-sintering: The ceramic green plate is placed in a high-purity nitrogen atmosphere furnace and heated to 700℃ at a rate of 0.8℃ / min. It is degreased and held for 3h to completely remove organic additives. Then it is heated to 1300℃ at a rate of 2.5℃ / min and pre-sintered for 2.5h to obtain a pre-sintered green body with a density of 80%.

[0060] (4) Semi-finishing: The sealing surface and positioning holes of the pre-sintered blank are semi-finished using diamond grinding wheels. The dimensional accuracy is controlled within ±20μm and the surface roughness Ra≤1.6μm. Then, the blank is ultrasonically cleaned with anhydrous ethanol for 15min and vacuum dried at 100℃ for later use.

[0061] (5) Densification sintering: The semi-finished green body is placed in a high-purity nitrogen atmosphere sintering furnace and heated to 1900℃ at a rate of 5℃ / min and held for 3h for pressureless densification sintering. After completion, it is cooled to room temperature with the furnace to obtain ceramic heat exchange plates with microchannel structure with a density ≥99.5%.

[0062] (6) Precision trimming and cleaning: The first microchannel, the second microchannel and the sealing surface of the sintered ceramic heat exchange plate are precisely trimmed using a femtosecond laser to remove slight deformation during the sintering process. The dimensional accuracy is controlled within ±2μm and the surface roughness Ra of the sealing surface is ≤0.2μm. After ultrasonic cleaning with anhydrous ethanol for 25min, it is vacuum dried at 120℃ for 12h for later use.

[0063] (7) Sealing and stacking: A 15μm thick layer of nano-sized ceramic powder solder is pre-coated on the sealing surface of the ceramic heat exchange plate. The composition of the solder is consistent with that of the heat-conducting layer, and the particle size is 35nm. The multilayer ceramic heat exchange plates are aligned and stacked, and placed in a high-purity nitrogen atmosphere diffusion welding furnace. The furnace is kept at 1700℃ and 3MPa for 2 hours to achieve low-temperature diffusion welding sealing.

[0064] (8) Assembly and testing: The welded ceramic heat exchange plates are stacked into the shell. The flexible sealing component uses the elastic ceramic fiber buffer bushing and graphite composite gasket to achieve flange-type flexible sealing. After assembly, the air tightness test, pressure test and heat exchange performance test are carried out in sequence. The finished product is obtained after passing the test.

[0065] Example 2:

[0066] This embodiment provides a modular high-temperature heat exchanger adapted to a 10MW-level solar thermal molten salt-sCO2 power generation system. Specific parameters are as follows:

[0067] Multiphase ceramic materials resistant to dual-media corrosion:

[0068] It includes a first surface layer, a thermally conductive layer, and a second surface layer, which are sequentially arranged. The first surface layer corresponds to the molten salt side, and the second surface layer corresponds to the sCO2 side. The total thickness is 3mm, with the first surface layer being 200μm, the thermally conductive layer being 2600μm, and the second surface layer being 200μm.

[0069] The raw materials for the first surface layer include the following components: 75wt% α-Al2O3 powder, 20wt% β-SiC powder, 4wt% Y2O3 sintering aid, and 1wt% La2O3 sintering aid;

[0070] The raw materials for the thermally conductive layer include the following components: 50wt% β-SiC powder, 45wt% α-Si3N4 whiskers, 4wt% Yb2O3 sintering aid, and 1wt% Sc2O3 sintering aid;

[0071] The raw materials for the second surface layer include the following components: 85wt% α-Si3N4 powder, 8wt% β-SiC powder, 1wt% Y2O3 sintering aid, 0.5wt% Sc2O3 sintering aid, 3wt% h-BN nanosheets, and 2.5wt% 3Y-TZP nano-ZrO2 powder. The h-BN nanosheets are pre-coated with a 50nm thick SiC layer by chemical vapor deposition. The coated h-BN nanosheets have a particle size of 150nm and a thickness of 20nm.

[0072] Among them, β-SiC powder is a submicron-sized high-purity powder with a purity ≥99.9% and a particle size of 1.5μm; α-Si3N4 whiskers have an aspect ratio ≥20 and a purity ≥99.5%; Y2O3 sintering aid, La2O3 sintering aid, Yb2O3 sintering aid, and Sc2O3 sintering aid are all nano-sized powders with a purity ≥99.99%.

[0073] Heat exchangers using the aforementioned dual-medium corrosion resistant multiphase ceramic materials:

[0074] The system comprises 80 layers of stacked ceramic heat exchange plates, a shell, and a flexible sealing assembly. The ceramic heat exchange plates are made of a dual-media corrosion-resistant multiphase ceramic material, with their opposite sides being a first surface layer and a second surface layer, respectively. The shell is fitted over the stacked ceramic heat exchange plates. The ceramic heat exchange plates measure 400mm × 400mm × 3mm. Ten sets of heat exchangers are modularly connected in parallel, with a total heat exchange area ≥ 2000m². 2 It is suitable for high-flow-rate operating conditions of 10MW.

[0075] The flexible sealing assembly comprises an elastic ceramic fiber buffer bushing and a graphite composite sealing gasket. The ceramic fiber buffer bushing is positioned between the edge of the ceramic heat exchange plate stack and the outer shell, while the graphite composite sealing gasket is positioned at the top and bottom ends of the ceramic heat exchange plates. The elastic ceramic fiber buffer bushing is a high-silica ceramic fiber woven structure with a thickness of 1 mm and a compression rate ≥15%. The graphite composite sealing gasket is a flexible graphite-stainless steel reinforced composite material with a thickness of 2 mm. The entire assembly is mechanically tightened using a flange.

[0076] The first surface layer has a first microchannel with dimensions of 500 μm width, 300 μm depth, and a spacing of 800 μm. Inside the first microchannel are 50 μm high herringbone ribs, the height of which is less than the depth of the first microchannel, and the included angle of the herringbone ribs is 60°. These ribs are evenly spaced along the fluid flow direction. The second surface layer has a second microchannel with dimensions of 200 μm width, 200 μm depth, and a pitch of 400 μm. Inside the second microchannel are diamond-shaped baffles, which are staggered along the fluid flow direction. The first and second microchannels are staggered perpendicular to the flow direction, so that the planar areas on adjacent ceramic heat exchange plates without the first or second microchannels act as sealing surfaces for each other.

[0077] A 20mm thick nanoporous calcium silicate ceramic heat insulation layer is also provided between the outer shell and the flexible sealing component; an 800μm thick alumina ceramic anti-corrosion coating is sprayed on the inner wall of the outer shell.

[0078] The method for preparing the above-mentioned heat exchanger includes the following steps:

[0079] (1) Raw material pretreatment: Weigh the raw material powder according to the formula of the first surface layer, the heat-conducting layer and the second surface layer in the multiphase ceramic material, add anhydrous ethanol solvent, ammonium polyacrylate dispersant and PVB binder in sequence, and ball mill for 48h to obtain three ceramic slurries with solid content ≥55wt% and viscosity 10000mPa·s respectively.

[0080] (2) Green body forming: A multi-layer co-casting process is adopted, in which the first surface layer, the heat-conducting layer and the second surface layer are cast in sequence to form a green body with a three-layer integrated gradient structure in one go. The total thickness of the green body is controlled at 3.6 mm. Through a precision mold hot pressing process, the pressure is controlled at 10 MPa, the holding time is 60 s and the hot pressing temperature is 35 ℃. In the state of the green body not drying, the corresponding first microchannel and second microchannel are pre-made on the first surface layer and the second surface layer respectively. After drying at a constant temperature and humidity of 30-40 ℃ for 48 h, a ceramic green body plate with microchannel structure is obtained.

[0081] (3) Degreasing and pre-sintering: The ceramic green plate is placed in a high-purity nitrogen atmosphere furnace and heated to 800°C at a rate of 1°C / min. It is degreased and held for 4 hours to completely remove organic additives. Then, it is heated to 1400°C at a rate of 3°C / min and pre-sintered for 3 hours to obtain a pre-sintered green body with a density of 85%.

[0082] (4) Semi-finishing: The sealing surface and positioning holes of the pre-sintered blank are semi-finished using diamond grinding wheels. The dimensional accuracy is controlled within ±20μm and the surface roughness Ra≤1.6μm. Then, the blank is ultrasonically cleaned with anhydrous ethanol for 20min and vacuum dried at 100℃ for later use.

[0083] (5) Densification sintering: The semi-finished green body is placed in a high-purity nitrogen atmosphere sintering furnace and heated to 1950℃ at a rate of 6℃ / min and held for 4h for pressureless densification sintering. After completion, it is cooled to room temperature with the furnace to obtain ceramic heat exchange plates with microchannel structure and a density ≥99.5%.

[0084] (6) Precision trimming and cleaning: The first microchannel, the second microchannel and the sealing surface of the sintered ceramic heat exchange plate are precisely trimmed by femtosecond laser to remove slight deformation during the sintering process. The dimensional accuracy is controlled within ±2μm and the surface roughness Ra of the sealing surface is ≤0.2μm. After ultrasonic cleaning with anhydrous ethanol for 30 min, it is vacuum dried at 120℃ for 12 h for later use.

[0085] (7) Sealing and stacking: A 20μm thick layer of nano-sized ceramic powder solder is pre-coated on the sealing surface of the ceramic heat exchange plate. The composition of the solder is consistent with that of the heat-conducting layer, and the particle size is 50nm. The multilayer ceramic heat exchange plates are aligned and stacked, and placed in a high-purity nitrogen atmosphere diffusion welding furnace. The furnace is kept at 1750℃ and 5MPa for 3h to achieve low-temperature diffusion welding sealing.

[0086] (8) Assembly and testing: The welded ceramic heat exchange plates are stacked into the shell. The flexible sealing component uses the elastic ceramic fiber buffer bushing and graphite composite gasket to achieve flange-type flexible sealing. After assembly, the air tightness test, pressure test and heat exchange performance test are carried out in sequence. The finished product is obtained after passing the test.

[0087] Example 3:

[0088] This embodiment provides a high-temperature heat exchanger adapted to a 0.5MW-class small-scale solar thermal molten salt-sCO2 power generation system. Specific parameters are as follows:

[0089] Multiphase ceramic materials resistant to dual-media corrosion:

[0090] It includes a first surface layer, a thermally conductive layer, and a second surface layer, which are sequentially arranged. The first surface layer corresponds to the molten salt side, and the second surface layer corresponds to the sCO2 side. The total thickness is 1 mm, of which the first surface layer is 50 μm, the thermally conductive layer is 900 μm, and the second surface layer is 50 μm.

[0091] The raw materials for the first surface layer include the following components: 85wt% α-Al2O3 powder, 10wt% β-SiC powder, 2wt% Y2O3 sintering aid, and 3wt% La2O3 sintering aid;

[0092] The raw materials for the thermally conductive layer include the following components: 60wt% β-SiC powder, 35wt% α-Si3N4 whiskers, 2wt% Yb2O3 sintering aid, and 3wt% Sc2O3 sintering aid;

[0093] The raw materials for the second surface layer include the following components: 90wt% α-Si3N4 powder, 3wt% β-SiC powder, 1wt% Y2O3 sintering aid, 1.5wt% Sc2O3 sintering aid, 2.5wt% h-BN nanosheets, and 2wt% 3Y-TZP nano-ZrO2 powder. The h-BN nanosheets are pre-coated with a 50nm thick SiC layer by chemical vapor deposition. The coated h-BN nanosheets have a particle size of 100nm and a thickness of 10nm.

[0094] Among them, β-SiC powder is a submicron-sized high-purity powder with a purity ≥99.9% and a particle size of 0.5μm; α-Si3N4 whiskers have an aspect ratio ≥20 and a purity ≥99.5%; Y2O3 sintering aid, La2O3 sintering aid, Yb2O3 sintering aid, and Sc2O3 sintering aid are all nano-sized powders with a purity ≥99.99%.

[0095] Heat exchangers using the aforementioned dual-medium corrosion resistant multiphase ceramic materials:

[0096] The device comprises 50 stacked ceramic heat exchange plates, a shell, and a flexible sealing assembly. The ceramic heat exchange plates are made of the aforementioned dual-media corrosion-resistant multiphase ceramic material, with their two opposite sides being the first and second surface layers, respectively. The shell is fitted over the stacked ceramic heat exchange plates. The ceramic heat exchange plates have dimensions of 200mm × 200mm × 1mm.

[0097] The flexible sealing assembly comprises an elastic ceramic fiber buffer bushing and a graphite composite sealing gasket. The ceramic fiber buffer bushing is positioned between the edge of the ceramic heat exchange plate stack and the outer shell, while the graphite composite sealing gasket is positioned at the top and bottom ends of the ceramic heat exchange plates. The elastic ceramic fiber buffer bushing is a high-silica ceramic fiber woven structure with a thickness of 0.5 mm and a compression rate ≥15%. The graphite composite sealing gasket is a flexible graphite-stainless steel reinforced composite material with a thickness of 1 mm. The entire assembly is mechanically tightened using a flange.

[0098] The first surface layer has a first microchannel with dimensions of 500 μm width, 300 μm depth, and a spacing of 800 μm. Inside the first microchannel are 50 μm high herringbone ribs, the height of which is less than the depth of the first microchannel, and the included angle of the herringbone ribs is 30°. These ribs are evenly spaced along the fluid flow direction. The second surface layer has a second microchannel with dimensions of 200 μm width, 200 μm depth, and a pitch of 400 μm. Inside the second microchannel are diamond-shaped baffles, which are staggered along the fluid flow direction. The first and second microchannels are staggered perpendicular to the flow direction, so that the planar areas on adjacent ceramic heat exchange plates without the first or second microchannels act as sealing surfaces for each other.

[0099] A 10mm thick nanoporous calcium silicate ceramic heat insulation layer is also provided between the outer shell and the flexible sealing component; the inner wall of the outer shell is sprayed with a 500μm thick alumina ceramic anti-corrosion coating.

[0100] The method for preparing the above-mentioned heat exchanger includes the following steps:

[0101] (1) Raw material pretreatment: Weigh the raw material powder according to the formula of the first surface layer, the heat-conducting layer and the second surface layer in the multiphase ceramic material, add anhydrous ethanol solvent, ammonium polyacrylate dispersant and PVB binder in sequence, and ball mill for 24 hours to obtain three ceramic slurries with solid content ≥55wt% and viscosity 5000mPa·s respectively.

[0102] (2) Green body forming: A multi-layer co-casting process is adopted, in which the first surface layer, the heat-conducting layer and the second surface layer are cast in sequence to form a green body with a three-layer integrated gradient structure in one go. The total thickness of the green body is controlled at 1.2 mm. Through a precision mold hot pressing process, the pressure is controlled at 5 MPa, the holding time is 30 s and the hot pressing temperature is 25 ℃. In the state of the green body not drying, the corresponding first microchannel and second microchannel are pre-made on the first surface layer and the second surface layer respectively. After drying at 30 ℃ constant temperature and humidity for 24 h, a ceramic green body plate with microchannel structure is obtained.

[0103] (3) Degreasing and pre-sintering: The ceramic green plate is placed in a high-purity nitrogen atmosphere furnace and heated to 600℃ at a rate of 0.5℃ / min. It is degreased and held for 2 hours to completely remove organic additives. Then, it is heated to 1200℃ at a rate of 2℃ / min and pre-sintered for 2 hours to obtain a pre-sintered green body with a density of 75%.

[0104] (4) Semi-finishing: The sealing surface and positioning holes of the pre-sintered blank are semi-finished using diamond grinding wheels. The dimensional accuracy is controlled within ±20μm and the surface roughness Ra≤1.6μm. Then, the blank is ultrasonically cleaned with anhydrous ethanol for 10min and vacuum dried at 100℃ for later use.

[0105] (5) Densification sintering: The semi-finished green body is placed in a high-purity nitrogen atmosphere sintering furnace and heated to 1850℃ at a rate of 4℃ / min and held for 2h for pressureless densification sintering. After completion, it is cooled to room temperature with the furnace to obtain ceramic heat exchange plates with microchannel structure and a density ≥99.5%.

[0106] (6) Precision trimming and cleaning: The first microchannel, the second microchannel and the sealing surface of the sintered ceramic heat exchange plate are precisely trimmed by femtosecond laser to remove slight deformation during the sintering process. The dimensional accuracy is controlled within ±2μm and the surface roughness Ra of the sealing surface is ≤0.2μm. After ultrasonic cleaning with anhydrous ethanol for 20min, it is vacuum dried at 120℃ for 12h for later use.

[0107] (7) Sealing and stacking: A 10μm thick layer of nano-sized ceramic powder solder is pre-coated on the sealing surface of the ceramic heat exchange plate. The composition of the solder is consistent with that of the heat-conducting layer, and the particle size is 20nm. The multilayer ceramic heat exchange plates are aligned and stacked, and placed in a diffusion welding furnace in a high-purity nitrogen atmosphere. The furnace is kept at 1650℃ and 1MPa for 1h to achieve low-temperature diffusion welding sealing.

[0108] (8) Assembly and testing: The welded ceramic heat exchange plates are stacked into the shell. The flexible sealing component uses the elastic ceramic fiber buffer bushing and graphite composite gasket to achieve flange-type flexible sealing. After assembly, the air tightness test, pressure test and heat exchange performance test are carried out in sequence. The finished product is obtained after passing the test.

[0109] Comparative Example 1:

[0110] The rest of the parts in this embodiment are the same as in embodiment 1, except that the ceramic heat exchange plates in the heat exchanger are made of single-phase pressureless sintered SiC ceramic.

[0111] Comparative Example 2:

[0112] The rest of the parts in this embodiment are the same as in embodiment 1, except that the ceramic heat exchange plates in the heat exchanger are made of SiC-Si3N4 multiphase ceramic.

[0113] Comparative Example 3:

[0114] The rest of the parts in this embodiment are the same as those in Embodiment 1. The difference is that the preparation method does not include degreasing, pre-sintering and semi-finishing steps. Instead, densification sintering is carried out directly, and then the ceramic heat exchange plates are connected by diffusion welding at 2100℃.

[0115] In this embodiment, the microchannel deformation of the green ceramic heat exchange plate after sintering is ≥15%, and the dimensional accuracy cannot meet the requirements; the flatness of the sealing surface is poor, and diffusion welding cannot achieve effective bonding. The interface bonding strength is only 45% of that of the base material, resulting in false welding and leakage; after high-temperature welding, the ceramic grains grow more than 3 times, the room temperature thermal conductivity drops to below 120W / (m·K), the performance decreases by 35%, and the yield is only 42%.

[0116] The parameters of the ceramic heat exchange plates in Examples 1-3 and Comparative Examples 1-2 were compared, and the results are shown in Table 1:

[0117]

[0118] Table 1

[0119] As shown in Table 1, the multiphase ceramic material processed in the embodiments of the present invention, while maintaining high thermal conductivity, has significantly better mechanical strength and significantly superior corrosion resistance compared with the prior art, and can better meet the heat exchange requirements of molten salt-sCO2 power generation systems.

[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A multiphase ceramic material resistant to dual-media corrosion, characterized in that: It includes a first surface layer, a heat-conducting layer and a second surface layer arranged in sequence. The first surface layer and the second surface layer sandwich the heat-conducting layer inside to form an integral structure. The thickness of the heat-conducting layer accounts for more than 80% of the total thickness. The raw materials for the first surface layer include the following components: 75-85wt% α-Al2O3 powder, 10-20wt% β-SiC powder, 2-4wt% Y2O3 sintering aid, and 1-3wt% La2O3 sintering aid; The raw materials of the thermally conductive layer include the following components: 50-60wt% β-SiC powder, 35-45wt% α-Si3N4 whiskers, 2-4wt% Yb2O3 sintering aid, and 1-3wt% Sc2O3 sintering aid; The raw materials for the second surface layer include the following components: 85-95wt% α-Si3N4 powder, 3-8wt% β-SiC powder, 1-3wt% Y2O3 sintering aid, 0.5-1.5wt% Sc2O3 sintering aid, 1-3wt% h-BN nanosheets, and 1-3wt% 3Y-TZP nano ZrO2 powder.

2. The dual-media corrosion resistant multiphase ceramic material as described in claim 1, characterized in that: The β-SiC powder is a submicron-sized high-purity powder with a purity ≥99.9% and a particle size of 0.5-1μm; the α-Si3N4 whiskers have an aspect ratio ≥20 and a purity ≥99.5%; the Y2O3 sintering aid, La2O3 sintering aid, Yb2O3 sintering aid, and Sc2O3 sintering aid are all nano-sized powders with a purity ≥99.99%.

3. The dual-media corrosion resistant multiphase ceramic material as described in claim 1, characterized in that: In the second surface layer, h-BN nanosheets are pre-coated with a 50-100 nm thick SiC layer by chemical vapor deposition. The coated h-BN nanosheets have a particle size of 100-200 nm and a thickness of 10-20 nm.

4. A heat exchanger employing the dual-medium corrosion-resistant multiphase ceramic material as described in any one of claims 1-3, characterized in that: The invention includes multi-layered stacked ceramic heat exchange plates, a housing, and a flexible sealing assembly. The ceramic heat exchange plates are made of the dual-media corrosion-resistant multiphase ceramic material, with two opposite sides being a first surface layer and a second surface layer, respectively. The housing is fitted over the stacked ceramic heat exchange plates, and the flexible sealing assembly is disposed between the housing and the stacked ceramic heat exchange plates. The first surface layer is provided with a first microchannel, and the second surface layer is provided with a second microchannel. The first microchannel and the second microchannel are arranged alternately along the direction perpendicular to the flow, so that the planar areas on adjacent ceramic heat exchange plates that are not provided with the first microchannel or the second microchannel are mutually sealing surfaces.

5. The heat exchanger as described in claim 4, characterized in that: The flexible sealing assembly includes an elastic ceramic fiber buffer bushing and a graphite composite sealing gasket. The ceramic fiber buffer bushing is filled between the edge of the ceramic heat exchange plate stack and the outer shell, and the graphite composite sealing gasket is disposed at the upper and lower ends of the ceramic heat exchange plate.

6. The heat exchanger as described in claim 4, characterized in that: The first microchannel is provided with herringbone ribs inside, the height of which is less than the depth of the first microchannel, and the included angle of the herringbone ribs is 30°-60°, and they are arranged at equal intervals along the fluid flow direction; the second microchannel is provided with rhomboid turbulence columns inside, and the rhomboid turbulence columns are arranged alternately along the fluid flow direction.

7. The heat exchanger as described in claim 4, characterized in that: The elastic ceramic fiber buffer bushing has a high-silica ceramic fiber woven structure with a thickness of 0.5-1mm and a compression of ≥15%; the graphite composite sealing gasket is a flexible graphite-stainless steel reinforced composite material with a thickness of 1-2mm.

8. The heat exchanger as described in claim 4, characterized in that: A nanoporous calcium silicate ceramic heat insulation layer with a thickness of 10-20 mm is also provided between the outer shell and the flexible sealing component; an alumina ceramic anti-corrosion coating with a thickness of 500-800 μm is sprayed on the inner wall of the outer shell.

9. A method for preparing a heat exchanger as described in any one of claims 4-8, characterized in that, Includes the following steps: S1. Raw material pretreatment: Weigh the raw material powder according to the formula of the first surface layer, the thermally conductive layer and the second surface layer in the multiphase ceramic material, add anhydrous ethanol solvent, ammonium polyacrylate dispersant and PVB binder in sequence, and ball mill for 24-48h to obtain three ceramic slurries with solid content ≥55wt% and viscosity 5000-10000mPa·s respectively. S2. Green body forming: A multi-layer co-casting process is adopted, in which the first surface layer, the heat-conducting layer and the second surface layer are cast in sequence to form a green body with a three-layer integrated gradient structure in one go. The total thickness of the green body is controlled between 1.2-3.6mm. Using a precision mold hot pressing process, corresponding first and second microchannels are pre-fabricated on the first and second surface layers respectively in the undried state of the green body; after drying at a constant temperature and humidity of 30-40℃ for 24-48 hours, ceramic green body plates with microchannel structures are obtained. S3. Degreasing and Pre-sintering: Place the ceramic green sheet in a high-purity nitrogen atmosphere furnace and heat it to 600-800℃ at a rate of 0.5-1℃ / min. Degrease and hold for 2-4 hours to completely remove organic additives. Then heat it to 1200-1400℃ at a rate of 2-3℃ / min and pre-sinter for 2-3 hours to obtain a pre-sintered green body with a density of 75%-85%. S4. Semi-finishing: The sealing surface and positioning holes of the pre-sintered blank are semi-finished using a diamond grinding wheel, with dimensional accuracy controlled within ±20μm and surface roughness Ra≤1.6μm; then ultrasonically cleaned with anhydrous ethanol for 10-20min and vacuum dried for later use. S5. Densification sintering: The semi-finished green body is placed in a high-purity nitrogen atmosphere sintering furnace and heated to 1850-1950℃ at a rate of 4-6℃ / min and held for 2-4 hours for pressureless densification sintering. After completion, it is cooled to room temperature with the furnace to obtain ceramic heat exchange plates with microchannel structure and a density ≥99.5%. S6. Precision trimming and cleaning: The first microchannel, the second microchannel, and the sealing surface of the sintered ceramic heat exchange plate are precisely trimmed using a femtosecond laser to remove slight deformations during the sintering process. The dimensional accuracy is controlled within ±2μm, and the surface roughness Ra of the sealing surface is ≤0.2μm. After ultrasonic cleaning with anhydrous ethanol for 20-30 minutes, the plate is vacuum dried for later use. S7. Sealing and Stacking: Pre-coat the sealing surface of the ceramic heat exchange plate with a 10-20μm thick layer of nano-sized ceramic powder solder. The solder composition is consistent with the composition of the heat-conducting layer, and the particle size is 20-50nm. Align and stack the multi-layer ceramic heat exchange plates, place them in a high-purity nitrogen atmosphere diffusion welding furnace, and keep them at 1650-1750℃ and 1-5MPa for 1-3 hours to achieve low-temperature diffusion welding sealing. S8. Assembly and Inspection: The welded ceramic heat exchange plates are stacked into the shell. The flexible sealing component uses an elastic ceramic fiber buffer bushing and a graphite composite gasket to achieve a flange-type flexible seal. After assembly, the air tightness test, pressure test, and heat exchange performance test are carried out in sequence. The finished product is obtained after passing the test.

10. The preparation method according to claim 9, characterized in that: In step S2, the pressure of the precision mold hot pressing process is 5-10 MPa, the holding time is 30-60 s, and the hot pressing temperature is 25-35℃.